Study on Control Strategy of Electro-Hydraulic Servo Loading System - Ju Tian (Institute of Advanced Engineering and Science, 2013)
Since extraneous torque is the key factor to affect the accuracy of electro-hydraulic servo loading system, the forming mechanism of extraneous torque was discussed in this work. And then several design methods of loading system controller based on modern control theory were introduced, such as internal model control, Cerebella model articulation control and adaptive backstepping control. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3246